Hamka's Concept of Tazkiyatun Nafs and Its Relevance as a Solution to Overcome Insecurity - Nur Hadi Ihsan; Faris Alfi Fauzi; Ridwan Abdul Jalal; Rahmat Ardi Nur Rifa Da'i (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2026)
Insecurity is a common psychological disorder resulting from the imbalance between reason and desires. HAMKA, a prominent Sufi scholar, offers the concept of Tazkiyatun Nafs (soul purification) as a solution to address this phenomenon. This study analyzes HAMKA's concept of Tazkiyatun Nafs in Modern Sufism as a spiritual solution to the phenomenon of insecurity in the modern era, which is exacerbated by social media pressure and self-comparison. Researchers in this literature review used textual analysis of HAMKA's works and comparisons with al-Ghazali's thoughts and Western psychological approaches such as CBT, with source triangulation for validity. The results show that Tazkiyatun Nafs—through the stages of takhalli, tahalli, and tajalli—eradicates insecurity in the form of body image, social, professional, relationship, financial, emotional, and intellectual, with the principles of ikhlas, tawakkal, muraqabah, and qana'ah that are more holistic than secular therapy. The researchers' conclusions emphasize the relevance of HAMKA's modern Sufism for faith-based mental health, contributing to the study of contemporary Sufism and the practice of Islamic psychology.